Value of social capital: Revisiting theoretical and empirical premises of social capital - Tuominen, Minna (fi=Turun yliopisto|en=University of Turku|, 2024)
Social capital is one of the most treasured concepts in the social sciences. However, the coexistence of several theories on social capital has led to multiplicity of definitions and operationalisations. Consequently, the corpus of social capital research consists of numerous studies, the results of which do not constitute a cumulative pool of knowledge. This dissertation contributes to the existing literature by providing further evidence of the associations among social capital, socioeconomic resources and well-being in different age and population groups. Specifically, this study aims to provide a more nuanced understanding of the relevance of socioeconomic resources to the dimensions of social capital, and of the relationship between these social capital dimensions and well-being, across different population groups. This is achieved by systematically breaking down the concept into more specific dimensions – social networks, trust and reciprocity – and exploring the assumed predictors and potential outcomes associated with each dimension. Theoretically, this dissertation draws from Pierre Bourdieu and Robert Putnam. This dissertation comprises four published articles based on four distinct cross-sectional datasets collected in Finland. Although the identified datasets contain essential information on the various dimensions of social capital, the cross-sectional nature of the data does not allow for the establishment of causality or directional relationships between these elements. Nonetheless, this research contributes to the literature by providing further evidence of correlational associations among these factors and outlining potential pathways for the flow of social capital. The first two articles focus on the supposed origins of social capital and the last two on its expected outcomes. The first article centres on early adolescents who are just starting to build social lives independent of their parents. Building on the structural equation model and a non-representative convenience sample collected from adolescents aged 12–13 years and their parents, the article assesses how parents’ social capital and family socioeconomic resources relate to adolescents’ social networks, trust, and reciprocal behaviour. While previous literature has mainly focused on the socioeconomic gradient in social networks, the findings of the first article suggest that socioeconomic resources are also associated with other dimensions of social capital, especially trust and reciprocity, among adults, but less evidently among adolescents who grow up in contexts of relative equality. However, adult behaviour appears to serve as a model for shaping the social capital of adolescent children, and through the parents’ example, socioeconomic background indirectly extends its bearing on youngsters’ social capital. The second article explores the development of social capital among foreign-born migrants who are establishing social relationships afresh in their new home country, assessing the relevance of socioeconomic background in the process. The analysis builds on a multinomial logistic regression model using a large amount of representative survey data. The results of the second article suggest that socioeconomic resources are particularly important for migrants. Income emerges as the element most consistently associated with building social capital while settling in a new country. This may be related to the specific Finnish context, where the standard and cost of living are high. In striving for homophily with the locals, newcomers must earn a reasonably high income to be able to participate in social life according to the prevailing standards. Consequently, these findings suggest that the relationship between socioeconomic resources and social capital may not be constant over time; rather, the larger the inequality in society, the greater the significance of socioeconomic resources in building social capital. The third article turns again to adolescents, assessing how the different dimensions of social capital relate to their subjective well-being. This study applies linear and quantile regression analyses to representative survey data collected among 12–13-year-olds. The fourth article features a similar analysis of an adult population. The third and fourth articles support previous research, pointing to a strong positive relationship between social capital and well-being in both generations. The results indicate that in both generations, reciprocity and social trust are the most important factors for well-being. The social network dimension exhibits a substantially weaker but significant association with well-being in both generations. These findings suggest that the relationship between social capital and well-being is likely to persist stably across age groups. However, the findings also suggest that adolescents with lower levels of well-being experience more significant improvements for each unit increase in social capital, whereas among adults who experience a scarcity of primary resources, other factors alongside social capital appear to play a significant role in their well-being. In sum, this research contributes to the literature by demonstrating that the association between socioeconomic resources and social capital varies across different population groups. Combining past research with the present findings suggests that greater societal inequality enhances the significance of socioeconomic resources in shaping social capital. Trust and reciprocity are the dimensions most sensitive to socioeconomic variation. Additionally, the study highlights the stability in the relationship between social capital and well-being across populations, with trust and reciprocity showing the strongest associations with well-being among adults and adolescents.

Sosiaalisen pääoman arvo Sosiaalinen pääoma on yksi yhteiskuntatieteiden keskeisimmistä käsitteistä. Useiden sosiaalista pääomaa koskevien teorioiden rinnakkaiselo on kuitenkin johtanut määritelmien ja operationalisointien moninaisuuteen. Sen seurauksena sosiaalisen pääoman tutkimuksen korpus koostuu lukuisista tutkimuksista, joiden tulokset eivät kumuloidu yhteiseksi tietovarannoksi. Tämä väitöskirja täydentää olemassa olevaa kirjallisuutta tarjoamalla lisänäyttöä sosiaalisen pääoman, sosioekonomisten resurssien ja hyvinvoinnin välisistä yhteyksistä eri ikä- ja väestöryhmissä. Tarkasti ottaen tämän tutkimuksen tavoitteena on tarjota yksityiskohtaisempaa tietoa sosioekonomisten resurssien merkityksestä sosiaalisen pääoman eri ulottuvuuksien kannalta ja näiden ulottuvuuksien yhteydestä hyvinvointiin eri väestöryhmissä. Tämä tehdään purkamalla järjestelmällisesti sosiaalisen pääoman käsite tarkemmin määriteltyihin ulottuvuuksiin – sosiaalisiin verkostoihin, luottamukseen ja vastavuoroisuuteen – ja tutkimalla erikseen jokaista ulottuvuutta selittäviä tekijöitä sekä niiden mahdollisia seurauksia. Teoreettisesti väitöskirja ammentaa Pierre Bourdieun ja Robert Putnamin näkemyksistä. Tämä väitöskirja koostuu neljästä julkaistusta artikkelista, jotka perustuvat neljään erilliseen Suomessa kerättyyn poikkileikkausaineistoon. Vaikka aineistot sisältävät sosiaalisen pääoman eri ulottuvuuksien keskeisiä mittareita, niiden poikkileikkaava luonne ei salli syy-seuraussuhteiden tai eri elementtien välisten yhteyksien suunnan määrittämistä. Rajoituksistaan huolimatta tämä tutkimus tuo kirjallisuuteen lisää todisteita näiden tekijöiden välisistä korrelaatioyhteyksistä ja hahmottelee mahdollisia väyliä, joita pitkin sosiaalinen pääoma pääsee muodostumaan ja joita pitkin se puolestaan vaikuttaa eteenpäin. Kaksi ensimmäistä artikkelia keskittyvät sosiaalisen pääoman oletettuun alkuperään ja kaksi viimeistä sen mahdollisiin seurauksiin. Ensimmäinen artikkeli keskittyy varhaisnuoriin, jotka ovat vasta alkaneet rakentaa itsenäistä sosiaalista elämää riippumatta vanhemmistaan. Artikkelissa tutkitaan, miten vanhempien sosiaalinen pääoma ja perheen sosioekonomiset resurssit liittyvät nuorten sosiaalisiin verkostoihin, luottamukseen ja vastavuoroiseen käyttäytymiseen nojautumalla rakenneyhtälömallinnukseen ja 12–13-vuotiailta nuorilta ja heidän vanhemmiltaan kerättyyn ei-edustavaan mukavuusotokseen. Aiempi kirjallisuus on keskittynyt pääasiassa sosioekonomiseen eriarvoisuuteen sosiaalisissa verkostoissa, mutta ensimmäisen artikkelin löydökset viittaavat siihen, että sosioekonomiset resurssit liittyvät myös muihin sosiaalisen pääoman ulottuvuuksiin, erityisesti luottamukseen ja vastavuoroisuuteen aikuisten keskuudessa. Yhteys on kuitenkin selvästi heikompi nuorten keskuudessa, jotka kasvavat suhteellisen tasa-arvoisissa olosuhteissa. Aikuisten käyttäytyminen näyttää kuitenkin toimivan mallina, joka muovaa nuorten sosiaalista pääomaa, ja vanhempien esimerkin kautta sosioekonominen tausta vaikuttaa epäsuorasti myös nuorten sosiaaliseen pääomaan. Toinen artikkeli tutkii sosiaalisen pääoman kehitystä ulkomaalaisten maahanmuuttajien keskuudessa, jotka rakentavat sosiaalisia suhteita uudessa kotimaassaan, ja arvioi sosioekonomisen taustan merkitystä tässä prosessissa. Analyysi perustuu multinomilogistiseen regressiomalliin käyttäen laajamittaista edustavaa kyselyaineistoa. Toisen artikkelin tulokset viittaavat siihen, että sosioekonomiset resurssit ovat erityisen tärkeitä maahanmuuttajille. Tulot osoittautuvat tekijäksi, joka liittyy kaikkein johdonmukaisimmin sosiaalisen pääoman kartuttamiseen uuteen kotimaahan asettauduttaessa. Tämä saattaa liittyä erityisesti suomalaiseen kontekstiin, jossa elintaso ja -kustannukset ovat korkeat. Pyrkiessään samankaltaisuuteen paikallisten kanssa, uusien tulokkaiden on ansaittava kohtuullisen korkeat tulot voidakseen osallistua sosiaaliseen elämään vallitsevien standardien mukaisesti. Näiden löydösten perusteella sosioekonomisten resurssien ja sosiaalisen pääoman välinen suhde ei välttämättä säily vakiona ajan mittaan; sen sijaan yhteiskunnan eriarvoisuuden kasvaessa sosioekonomisten resurssien merkitys sosiaalisen pääoman rakentamisessa näyttäisi korostuvan. Kolmas artikkeli keskittyy jälleen nuoriin ja arvioi, kuinka sosiaalisen pääoman eri ulottuvuudet liittyvät heidän subjektiiviseen hyvinvointiinsa. Tämä tutkimus soveltaa lineaarisia ja kvantiiliregressioanalyysejä edustaviin kyselytietoihin, jotka on kerätty 12–13-vuotiailta. Neljännessä artikkelissa tehdään samankaltainen analyysi aikuisväestöstä. Kolmas ja neljäs artikkeli tukevat aiempaa tutkimusta tuoden esiin vahvan positiivisen yhteyden sosiaalisen pääoman ja hyvinvoinnin välillä molemmissa sukupolvissa. Näiden tulosten mukaan molemmissa sukupolvissa vastavuoroisuus ja sosiaalinen luottamus näyttävät olevan keskeisimmät hyvinvointiin vaikuttavat tekijät. Sosiaalisten verkostojen yhteys hyvinvointiin on huomattavasti heikompi, mutta kuitenkin merkittävä molemmissa sukupolvissa. Nämä havainnot viittaavat siihen, että sosiaalisen pääoman ja hyvinvoinnin välinen suhde säilyy todennäköisesti vakaana eri ikäryhmien välillä. Kuitenkin näiden tulosten mukaan nuoret, joiden hyvinvoinnin taso on alhainen, hyötyvät erityisen paljon sosiaalisen pääoman jokaisen yksikön lisääntymisestä. Sen sijaan aikuisten keskuudessa, jotka elävät resurssien niukkuudessa, muut tekijät sosiaalisen pääoman ohella näyttävät olevan merkittävässä roolissa heidän hyvinvointinsa kannalta. Yhteenvetona voidaan todeta, että tämä tutkimus täydentää kirjallisuutta osoittamalla, että sosioekonomisten resurssien ja sosiaalisen pääoman välinen yhteys vaihtelee eri väestöryhmissä. Aiempien tutkimusten ja tämän väitöskirjan tuloksia yhdistelemällä voidaan todeta, että yhteiskunnallisen eriarvoisuuden kasvaessa sosioekonomisten resurssien merkitys sosiaalisen pääoman muodostumisessa lisääntyy. Luottamuksen ja vastavuoroisuuden ulottuvuudet ovat herkimmät sosioekonomiselle vaihtelulle. Samanaikaisesti tämä tutkimus korostaa sosiaalisen pääoman ja hyvinvoinnin välisen suhteen vakautta eri väestöryhmissä; luottamus ja vastavuoroisuus muodostavat vahvimmat yhteydet aikuisten ja nuorten hyvinvointiin.